Gradients of Taxonomic Diversity among Local Floras in the Russian Arctic - Khitun, O V; Chinenko, S V; Zverev, A A; Koroleva, T M; Petrovsky, V V; Pospelov, I N; Pospelova, E B (KnE Life Sciences, 2018)
Latitudinal and longitudinal changes in taxonomic variables were analyzed in 319 local floras in the Russian Arctic. Within the studied segment of latitudinal gradient, most changes can be described in terms of linear regression with negative coefficients (a number of species, genera and families), or positive coefficients (a proportion of the leading families and genera). However, the mean number of species in a family or genus almost does not change with increasing latitude, although it slightly increases as one moves eastward. The proportion of monocots does not correlate with latitude, but slightly decreases as one moves eastward. Proportions of various families change asynchronously. Although correlation with longitude was less pronounced, mean species richness was specific to many subprovinces, even within a certain subzone. These differences reflect both the diversity of landscapes and the history of flora formation. Keywords: the Arctic, local floras, latitudinal and longitudinal gradient, floristic subprovinces